2016
DOI: 10.3892/or.2016.4728
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits cell cycle progression by targeting Aurora kinase A and Polo-like kinase 1 in breast cancer cells

Abstract: The Aurora protein kinase (AURKA) and the Polo-like kinase-1 (PLK1) activate the cell cycle, and they are considered promising druggable targets in cancer therapy. However, resistance to chemotherapy and to specific small‑molecule inhibitors is common in cancer patients; thus alternative therapeutic approaches are needed to overcome clinical resistance. Here, we showed that the dietary compound resveratrol suppressed the cell cycle by targeting AURKA and PLK1 kinases. First, we identified genes modulated by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Resveratrol (RVT) a natural polyphenolic compound found in grapes and berries has been widely studied and is considered as an anti‐cancer, anti‐diabetes, cardioprotective, and anti‐inflammatory molecule . Its molecular targets include AKT, mTOR, NF‐kB, STAT, MAPK, AURKA, and PLK1, resulting in their inactivation and subsequent inhibition of cell proliferation . In another hand, RVT was shown to induce cell cycle arrest by activation of p53, p27, p21, and p16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol (RVT) a natural polyphenolic compound found in grapes and berries has been widely studied and is considered as an anti‐cancer, anti‐diabetes, cardioprotective, and anti‐inflammatory molecule . Its molecular targets include AKT, mTOR, NF‐kB, STAT, MAPK, AURKA, and PLK1, resulting in their inactivation and subsequent inhibition of cell proliferation . In another hand, RVT was shown to induce cell cycle arrest by activation of p53, p27, p21, and p16 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Its molecular targets include AKT, mTOR, NF-kB, STAT, MAPK, AURKA, and PLK1, resulting in their inactivation and subsequent inhibition of cell proliferation. 15,16 In another hand, RVT was shown to induce cell cycle arrest by activation of p53, p27, p21, and p16. [17][18][19] A plethora of studies have shown RVT affect multiple epigenetic events, including DNA methyltransferases or DNMTs, sirtuin HDACs (SIRT1 and SIRT2), and lysine-specific demethylase 1.…”
Section: Introductionmentioning
confidence: 99%
“…MCF7/T46D and MDA-MB-231 cells were seeded at a density of 5000 cells/well in a 96-well plate and incubated overnight. Seeded cells were treated with ISO and Rsv for 48 h. Most of the previous studies reported the highest anti-cancer efficacy of Rsv following 48 h of treatment [49][50][51]. Therefore, we chose this time point to determine the anti-cancer effects of ISO.…”
Section: Measurement Of Cell Viability (Mtt Assay)mentioning
confidence: 99%
“…Treatment of mammary cancer in rats with high doses of resveratrol reduced cellular proliferation, increased apoptosis, and decreased angiogenesis in mammary epithelial cells via AKT inactivation and modulation of forkhead transcription factors, resulting in tumor suppression . A significant decrease in the expression of genes involved in the cell cycle, DNA repair, cytoskeleton organization, and angiogenesis after resveratrol treatment have been attributed to the downregulation of cell cycle activators, such as Aurora protein kinase (AURKA) and the Polo‐like kinase‐1 (PLK1) . Furthermore, resveratrol has been shown to play a role in upregulation of death‐associated protein kinase 2 (DAPK2) and BCL2/adenovirus E1B 19‐kDa interacting protein 3 (BNIP3), as well as downregulation of fatty acid synthetase (FAS), in tumor microenvironments …”
Section: Angiogenic Mechanisms Of Resveratrol and Its Therapeutic Appmentioning
confidence: 99%
“…100 A significant decrease in the expression of genes involved in the cell cycle, DNA repair, cytoskeleton organization, and angiogenesis after resveratrol treatment have been attributed to the downregulation of cell cycle activators, such as Aurora protein kinase (AURKA) and the Polo-like kinase-1 (PLK1). 101 Furthermore, resveratrol has been shown to play a role in upregulation of death-associated protein kinase 2 (DAPK2) and BCL2/adenovirus E1B 19-kDa interacting protein 3 (BNIP3), as well as downregulation of fatty acid synthetase (FAS), in tumor microenvironments. 102 Prostate.…”
Section: Cancermentioning
confidence: 99%